LEGAL REVIEW ON CPTPP AND ITS IMPLICATION ON BUMIPUTERA’S POLICIES IN MALAYSIA GOVERNMENT PROCUREMENT - Haron, Muhammad Hanafi (Bank Indonesia, 2023)
The Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) is an open and multi trade agreement that significantly liberalizes international procurement Trans-Pacific markets. Chapter 15 of the CPTPP is covers government procurement. Malaysia signed and eventually ratified CPTPP later in 2022 and needs to incorporate Chapter 15 into its government procurement regulations. Having said this, the question remains on how features of Chapter 15 will stand and comport with the existing protection mechanisms that are practiced by Malaysia in its government procurement regime, namely Bumiputera policy. Malaysia also has claimed some reservation and threshold amounts in the said Chapter under the Annexure 15-A of the State Schedule. Thus, the objective of this writing is, first, to review the existing legislation and regulations in Malaysia that cover government procurement. Then, it discusses how the ratification of the CPTPP will impact the existing Bumiputera policy practiced in government procurement ecosystems. Finally, this writing reviews the Government of Malaysia’s action and plan on government procurement post ratification of CPTPP. This study adopts a qualitative method that mainly relies on descriptive and analytical examinations of statutory provisions and relevant authorities. It concludes that Malaysia’s Bumiputera policy is still unflawed in the government procurement despite the ratification and adoption of Chapter 15 of the CPTPP. BNM as the financial policy advisor to the Government of Malaysia is not being statutorily vested with power to review and provide feedback on CPTPP to the government. This is due to the reservations and high price preferential system imposed by Malaysia for a much longer period before its finally fully incorporated and functional in Malaysia’s government procurement.